2018
DOI: 10.1108/ijppm-03-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of market competition, strategic orientation and adoption of green initiatives in Malaysian public listed companies

Abstract: Purpose The purpose of this paper is to examine the influence of intensity of market competition and strategic orientation on the adoption of green initiatives among public listed companies (PLCs) in Malaysia. Design/methodology/approach A questionnaire survey was distributed to all 921 PLCs, and 120 samples were analysed. This study used a statistical tool named partial least squares – structural equation modelling (PLS–SEM) for data analysis. Interviews were also conducted with a few selected companies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 54 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…The drive to adopt and deploy OSC is also motivated by manufacturing organisations' drive to sustain a competitive edge in a hypercompetitive business environment (Chavez et al, 2015;Li et al, 2019). Similarly, while taking into consideration the need to maximise profits for shareholders, organisational leaders are also under pressure to address stakeholder concerns of increased ES (Abdulaziz et al, 2017;Dumont, Sheng, & Deng, 2017;Merriman & Sen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The drive to adopt and deploy OSC is also motivated by manufacturing organisations' drive to sustain a competitive edge in a hypercompetitive business environment (Chavez et al, 2015;Li et al, 2019). Similarly, while taking into consideration the need to maximise profits for shareholders, organisational leaders are also under pressure to address stakeholder concerns of increased ES (Abdulaziz et al, 2017;Dumont, Sheng, & Deng, 2017;Merriman & Sen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most organizations currently are struggling with dual pressures of promulgating long-term business growth while operating in the hypercompetitive markets along with the need to alleviate the negative footprints of their operations (Jansson et al, 2017). Aziz et al (2018) too emphasized this challenge and shared how organizations currently walk on a tight rope of maintaining the financial stability of business and ensuring commitment to sustainability. Commitment to sustainability is expected to require organizations to harness relationships with their key stakeholders, such as investors, employees, customers and immediate social community, for accomplishing their sustainability agenda (Daily and Huang, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…sector studied in this study. Abdulaziz et al (2017) also found that mimetic pressures do not significantly affect green activities in Malaysian publicly listed businesses (PLCs). However, coercive and normative pressures are more important.…”
Section: Test Of Hypothesismentioning
confidence: 99%